Psychological Well-Being and South African Socio- Economic Stressors: The moderating role of Leaders creating Hope - Aysen, Savannah (University of the Witwatersrand, Johannesburg, 2024)
The current research study explored whether leaders creating hope in their employees moderates the relationship between South African socio-economic stressors and employee psychological well-being. Existing literature indicates that stressors have dire implications for the well-being of employees and that psychological capital is a meaningful resource to elevate deteriorating well-being (Slone et al., 1999; Charles et al., 2013). Moreover, research reveals the potential of leaders to create hope within their organisations which may aid in elevating deteriorating well-being levels (Yukl, 1998; Helland and Winston, 2005). Accordingly, this research aimed to explore whether leaders creating hope would moderate the relationship between South African socio-economic stressors and psychological well-being. This study utilised a quantitative non-experimental cross-sectional research design to explore the statistical relationships between South African socio-economic stressors, psychological well-being and leaders creating hope. Data was collected through an online self-report questionnaire (N=130). The questionnaire contained a self-developed demographic questionnaire, an adapted South African socio-economic stressors scale, the Psychological General Well-Being Index, and the adapted Leaders Creating Hope scale. Results of the study indicated that both South African socio-economic stressors and leaders creating hope were correlated with psychological well-being, and a multiple regression analysis revealed that both South African socio-economic stressors and leaders creating hope are predictors of psychological well-being within the sample. However, even though leaders creating hope was found to have a positive effect on psychological well-being it did not have a moderating effect on the relationship between South African socio-economic stressors and psychological well-being.
A research report Submitted in fulfillment of the requirements for a Master of Arts Organisational Psychology,, In the Faculty of Humanities , School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; South African socio-economic stressors; psychological capital hope; leaders; leaders creating hope; psychological well-being; SDG-3: Good health and well-being; SDG-8: Decent work and economic growth